European model of agriculture - Laurila, Ilkka P. (Maatalouden taloudellinen tutkimuslaitos, 2000)
The nucleus of the European model of agriculture (EMA) is a sector consisting of family farms producing, in an acceptable way, a wide set of public goods in addition to food and fibre. Because of the regional diversity and varying societal values and needs within Europe, the concept of EMA varies by region. The concept is closely linked to the concepts of multifunctional character of agriculture, and sustainable agriculture and rural development. In the discussions of agricultural trade, the EMA is linked to the non-trade concerns. The EMA is a policy theme and political statement that is currently used in agricultural, rural, environmental and trade discussions. The EMA is relevant in a number of global policy processes such as the WTO round and Rio UN Earth Summit 1992 processes (Convention on Biodiversity, and Agenda 21 on sustainable development), the Framework Convention on Climate Change signed in the Rio Summit, and the Commission on Sustainable Development, created in 1992 within the UN organisation. The EMA is also relevant in the implementation of Agenda 2000 reform of the CAP (Rural Development Plans, cross-compliance in support) and in the planning of the next CAP reform, which will be closely linked to the EU enlargement and results of the WTO round. The concept of EMA will be relevant in specifying future policies that shape the cultural landscape of Europe, viability of countryside, the city-countryside relationship, and agricultural production systems and their environmental effects. In the future, the EMA may become used more generally in the discussions on the future orientation of societies.
Keywords: Ma; Agenda 2007; monivaikutteisuus; julkishyödykkeet; maaseudun kehitys; perheviljelmät; maatalouden ympäristöpolitiikka; ei-kaupalliset kysymykset; WTO; Agenda 2007; agri-environmental policies; WTO; family farm; landscape; multifunctional character of agriculture; non-trade concerns; public good; rural development plans; SARD; viability of countryside